2008
DOI: 10.1097/01.jac.0000324666.98777.6d
|View full text |Cite
|
Sign up to set email alerts
|

SMS Text Message Healthcare Appointment Reminders in England

Abstract: Missed appointments place a costly and disruptive strain on National Health Service resources in England. One major source of missed appointments appears to be insufficient communication between patients and providers. SMS text messaging shows promise as a simple, cost-effective means of bridging this communications gap. SMS provides an instant and asynchronous means of communication that protects patient privacy. The potential for this technology is balanced, however, by the lack of high-quality evidence to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…); were reviews or commentaries which did not contain original data (Reda and Makhoul ; Callaghan ; Fahey ; Tomlinson ; Car et al. ; Cohen et al. ; Henderson ; Krishna, Boren, and Balas ); described programs to improve health outcomes other than attendance rates (Mao, Zhang, and Zhai ; Miloh et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…); were reviews or commentaries which did not contain original data (Reda and Makhoul ; Callaghan ; Fahey ; Tomlinson ; Car et al. ; Cohen et al. ; Henderson ; Krishna, Boren, and Balas ); described programs to improve health outcomes other than attendance rates (Mao, Zhang, and Zhai ; Miloh et al.…”
Section: Resultsmentioning
confidence: 99%
“…Using the search words, 53 articles were identified. Of these, 23 were excluded based on abstract because they described a survey of attendance rates (Martin, Perfect, and Mantle 2005;van Baar et al 2006;Brown et al 2006Brown et al , 2008Casey et al 2007;Hogan et al 2008;Hogg, Lomicky, and Weiner 2008;Crosby et al 2009;O'Connor et al 2009;Raine et al 2009); were reviews or commentaries which did not contain original data (Reda and Makhoul 2001;Callaghan 2003;Fahey 2003;Tomlinson 2003;Car et al 2008;Cohen et al 2008;Henderson 2008;Krishna, Boren, and Balas 2009); described programs to improve health outcomes other than attendance rates (Mao, Zhang, and Zhai 2008;Miloh et al 2009;Shapiro et al 2010;Pijnenborg et al 2010); or described electronic communication systems that did not use SMS reminders to improve attendance rates (Zingmond and Lenert 1993;Oddsson et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…9 They are used throughout the world across healthcare settings, with studies and reviews demonstrating increased appointment attendance. [10][11][12][13] A recent meta-analysis and systematic review showed 50% improvements in attendance (relative to when no notification was provided); 14 since this review was published, the use of technology is even more prevalent, with the use of smartphones almost doubling in the USA, (from 35% to 64% among adults). 15 No-one has yet assessed the effectiveness of the intervention with regard to study quality/risk of bias.…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, ERs have been used effectively to improve attendance rates for outpatient appointments [12e15]. However, more evidence is required to endorse the use of this type of reminder system [16].…”
Section: Strengths and Limitationsmentioning
confidence: 99%